Enhanced visualization of cell surface glycans via a hybridization chain reaction. Issue 43 (9th May 2019) - Wen, Xiaohong; Yuan, Baoyin; Zhang, Junxun; Meng, Xiangxian; Guo, Qiuping; Li, Lie; Li, Zenghui; Jiang, Huishan; Wang, Kemin
Abstract : We apply a DNA hybridization chain reaction (HCR) to achieve sensitively amplified imaging of cell surface glycosylation. Abstract : Herein, we apply a DNA hybridization chain reaction (HCR) to achieve sensitively amplified imaging of cell surface glycosylation with reduced non-natural monosaccharide units. This method is simple, efficient, sensitive, and possesses great potential to illuminate the pathways via which cell surface glycosylation regulates cell functions.